Evolution and Theology, or Theology of Evolution in the USA - Obirek, Stanisław (Studia religiologica, 2017)
The impact of Charles Darwin’s theory of evolution on religious thinking is beyond dispute. Darwin published his most important work on general biological evolution (On the Origins of Species) in 1859, and in 1871 he applied this theory to the origin of man (The Descent of Man, and Selection in Relation to Sex). From the beginning, most Christian churches rejected Darwin’s view, but most scientists accepted it as the most convincing explanation of the mechanisms of life. A new chap-ter in this controversy was opened by Richard Dawkins in 2006 with the publication of TheGod Delusion, in which he not only vigorously defended Darwin’s theory but also rejected any religious dimension of biological reality. An interesting alternative to Dawkins’s theory was elaborated by John F. Haught in his trilogy: God After Darwin: A Theology of Evolution (2000); Making Sense of Evolution: Darwin, God, and The Drama of Life (2010); and Resting on the Future: Catholic Theology for an Unfinished Universe (2015), in which he elaborated a theology of evolution where-in he reconciled the theory of evolution with Christian-Catholic theology. The aim of this essay is to ask to what extent this attempt is successful.